Anthropometric, metabolic, dietary and psychosocial profiles of underreporters of energy intake: a doubly labeled water study among overweight/obese postmenopausal women-a Montreal Ottawa New Emerging Team study - Karelis, A.D; Lavoie, M-E; Fontaine, J; Messier, V; Strychar, I; Rabasa-Lhoret, R; Doucet, E (European journal of clinical nutrition, 2010)
Background/Objectives: To analyze the anthropometric, metabolic, psychosocial and dietary profiles of underreporters, identified by the doubly labeled water technique, in a well-characterized population of overweight and obese postmenopausal women. Subjects/Methods: The study population consisted of 87 overweight and obese sedentary postmenopausal women (age: 57.7±4.8 years, body mass index: 32.4±4.6 kg/m2). Subjects were identified as underreporters based on the energy intake to energy expenditure ratio of <0.80. We measured (1) body composition (by dual-energy X-ray absorptiometry), (2) visceral fat (by computed tomography), (3) blood profile, (4) resting blood pressure, (5) peak oxygen consumption (VO2 peak), (6) total energy expenditure, (7) muscle strength and (8) psychosocial and dietary profiles. Results: Out of 87 subjects, 50 (57.5%) were identified as underreporting subjects in our cohort. Underreporters showed higher levels of body mass index, fat mass, visceral fat, hsC-reactive protein, perceived stress and percentage of energy from protein, as well as lower levels of VO2 peak, dietary intake of calcium, fiber, iron, vitamin B-1 and 6, as well as servings of fruit and vegetables. Logistic regression analysis showed that fat mass, odd ratio 1.068 (95% confidence interval 1.009-1.130) and perceived stress, odd ratio 1.084 (95% confidence interval 1.011-1.162) were independent characteristics of underreporters. Conclusions: Results from this study show significant differences in anthropometric, metabolic, psychosocial and dietary profiles between underreporters and non-underreporters in our cohort of overweight and obese postmenopausal women.